การวิจัยแบบมีส่วนร่วมเพื่อการจัดการทรัพยากรน้ำในลุ่มน้ำแม่สะเรียง จังหวัดแม่ฮ่องสอน - คุณประดิษฐ์, ทัตพร; นุ่มมีศรี, สุรศักดิ์; เขาดี, วรางคณา (Ganesha Journal, 2012)
[บทคัดย่อภาษาไทยไม่สมบูรณ์] The Participatory Action Research on Water resource Management in Mae Sariang Watershed, Mae Hong Son Province were studied. The Study on Bio-monitoring and Water Resources in Mae Sariang Watershed, Mae Hong Son Province by using aquatic organisms, benthic diatom, macroalgae, phytoplankton and aquatic insects and some physico-chemical technique carried out from September 2008 to March 2010. Seven sampling sites along the Mae Sariang River were chosen including MR1 Mae Umlong left, MR2 MAE Umlong right, MR3 Mae Umlong Middle, MR4 Pa kluy up, MR5 Pa kluy down, MR6 Ni muang and MR7 Ban Nam Dib Tambon Mae Yuam, Mae Sariang Province. Fifteen species of benthic diatom, and macroalgae and fourteen species of phytoplankton and 17 family of macroalgae were found. The diversity of aquatics organism shown that the Mae Sariang River is classified into the moderate abundance compare to the other rivers in northern Thailand. The water quality investigation by using ASPT, AARL-PP and AARL-PC Score revealed that the water quality in upper stream (MR1 and MR2) is classified to moderate to clean and downstream (MR3 to MR 7) is classified to moderate water quality. The overall water quality in Mae Sariang were moderate when compared with the standard water quality of Thailand. The water can use for household consumption by common treat and agricultural. This project is including the knowledge transferred to the local people such as student and local citizens. Two workshops were issued for communities/school including student, teacher and people in the research areas along the Mae Sariang River. The participants were studied for collecting aquatics samples, monitored and evaluated the water quality by themselves. The result from local researcher and the collecting sample by Chiang Mai Rajabhat University staff found that the macroalgae and aquatic insects could be used for water quality indicator and monitor in the Mae Sariang River. The water component that used for household consumption in Mae Sariang River was studied. The analysis of metal ions in water of Mae Sariang river community showed that there is calcium and magnesium at high level but some iron and zinc are found. The objective of this research to reduce these metal ions by modifying the structure of cellulose obtained from local plants for adsorption them. The best local plant was selected by considering the amount and characteristic of cellulose. In this research was investigated in many parameters such as the preparation of cellulose, two methods of cellulose modifications (type 1: phosphorylation reaction and type 2: using EDTAD as modifying agent), the equilibrium adsorption time and the effect of pH range of solution. Calcium ion and Magnesium ion are the representative of this testing because they are highly amount in water. The results showed that Leersia hexandra SW was the appropriate local plant which contained 30% cellulose after hydrolyzing with 0.2 M NaOH, 2 hr 30 min, 90oC. Cellulose was purified in 5% v/v HCl heated at 40oC for 1 hr. The equilibrium adsorption time was 30 min. Adsorption results showed that both modified celluloses can reduce metal ions in water similar to unmodified. Cellulose and modified cellulose type 1 can absorb calcium, magnesium and zinc in the basic pH range. Conversely, iron was adsorbed in acidic pH range. Whereas, modified cellulose type 2, which was studied only calcium and magnesium adsorption, can adsorp calcium and magnesium in both acidic and basic pH value. Another research is the participatory action research on pollution managements in Mae Sariang River. The two main objectives of this research with the title Water pollution management in basin area of Mae Sariang River, Mae Hong Son Province was lean on the first, For Studying the water pollution in basin area of Mae Sariang River and the second was to set the optimum pattern with this area and community proceeding by themselves in water pollution management. The important problem that brought about water pollution in Mae Sariang River was from soil sediment which contaminated in the river. These sediments had initiated from the soil which fell down to the ground after the bank of the river eroded. Also in the road construction from town leaded into many villages in that area, Grass or undergrowth mounting and burning for agriculture including the river dredging on the purpose of construction materials as soil and many reasons leaded to that problem. The second important problem was the garbage which produced from the entrepreneurs that proceeding their job on the bank of the river including the dung and litter from the cattle in water resources respectively. The ways to solve these problems by the researcher team accompanied with the community were seek for the pattern of an actual performing for all. The first thing of these was to set the community mapping which brought to know in overall problems. After that set in many activities to activate and restore Mae Sa-reang water shade such as Activities that reduced turbidity in the river, for example a dam for irrigation purposes in the forest, a banana or a betel palm planting in the water source area, set up fire protection line area for protection of the soil crumble especially on the area nearby the bank of the Mae Sa-reang river with the advantage of forest defending. Besides that to grow the conscious for teenagers and community in loving their river, the activities served by gathering all in the camp of the river conservation. After carried out all of activities that implement above brought all the people and the community executives of Mae Sariang district realized that their community could proceeding all the ways in solving problem by their own ability. From that reasons the executives were set all the activities in the new budget action plan for the new year plan about a natural resources management of the Mae Sariang district such as a water resources forest planting, Protection line of wildfire and A water resource forest and a fish heredity conservative. To succeed all the activities in that area that lead to solving problems at last.